2013
DOI: 10.1016/j.jacc.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedural Estimate of Individualized Bleeding Risk Impacts Physicians' Utilization of Bivalirudin During Percutaneous Coronary Intervention

Abstract: There was an increase in bivalirudin use and a lower incidence of bleeding after the incorporation of individualized bleeding risk estimates into clinical practice. This implementation led to a reversal of the risk-treatment paradox, through a rational increase in bivalirudin use in patients at intermediate and high bleeding risk and decreased use in lower-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Furthermore, knowing the patients' bleeding risk can impact physician behavior in terms of treatment used. 23 Although we did not examine the relationship between individual bleeding risk profile and treatment selection with our current study design, we found that these factors together explained 32.3% hospital variation in major bleeding rates. Therefore, defining optimal treatment selection based on risk factors might be a critical step to motivate appropriate use of antithrombotic treatments and further reduce bleeding complications.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, knowing the patients' bleeding risk can impact physician behavior in terms of treatment used. 23 Although we did not examine the relationship between individual bleeding risk profile and treatment selection with our current study design, we found that these factors together explained 32.3% hospital variation in major bleeding rates. Therefore, defining optimal treatment selection based on risk factors might be a critical step to motivate appropriate use of antithrombotic treatments and further reduce bleeding complications.…”
Section: Discussionmentioning
confidence: 76%
“…2 Periprocedural bleeding is not benign because data have shown an association between bleeding complications and morbidity and mortality. [17][18][19][20][21] For example, using the National Cardiovascular Data Registry CathPCI Registry, Rao et al 22 demonstrated a >30% increase in 30-day mortality in patients with PCI-related bleeding. When compared with TFI, TRI has consistently been shown to reduce access site bleeding (Figure 2), major vascular complications, and blood transfusions.…”
Section: Proposed Mechanisms For Reduced Mortality Bleeding Reductionmentioning
confidence: 99%
“…These changes in bivalirudin use were associated with reductions in bleeding complications in intermediate and high bleeding risk patients without increasing bleeding in low bleeding risk patients. 27 The current study is distinct in several ways. First, we used a shared electronic medical record to review all PCI cases from 3 distinct, independent, high-volume centers.…”
Section: Summary Of the Experience Future Directions And Challengesmentioning
confidence: 94%
“…3 To our knowledge, only 1 previous study has used the NCDR bleeding risk model for pre-PCI risk stratification. Rao et al 27 found that individualized bleeding risk estimates increased bivalirudin use in intermediate and high bleeding risk patients and decreased bivalirudin use in low bleeding risk patients. These changes in bivalirudin use were associated with reductions in bleeding complications in intermediate and high bleeding risk patients without increasing bleeding in low bleeding risk patients.…”
Section: Summary Of the Experience Future Directions And Challengesmentioning
confidence: 99%